Mindfulness and Smartphone Addiction: An SLR on Positive Psychological Interventions in Adolescents - Lia Humairoh; Anna Armeini Rangkuti; Iriani Indri Hapsari; Zarina Akbar (International Conference on Psychology and Education (ICPE), 2025)
Smartphone addiction among adolescents has emerged as a significant psychological concern in the digital era, marked by compulsive smartphone use, emotional dysregulation, and increased anxiety, depression, and sleep disturbances. Adolescents are particuraly vulnerable due to the critical stage of their social-emotional development and their hight exposure to digital devices. This literature review aims to examine the effectiveness of mindfulness-based interventions in reducing the psychological impact of smartphone addiction among adolescents. Ten relevant studies were reviewed and synthesized based on the type of interventions, target outcome, and application context. The results indicate that mindfulness-through approaches such as Mindfulness-Based Cognitive Therapy (MBCT), school-based mindfulness training, and self-awareness education can effectively reduce stress, improve emotional regulations, and minimize problematic smartphone use. The interventions were found to be applicable in both clinical and educational setting. In conclusion, mindfulness represents a promising strategy within the field of positive psychology to address smartphone addiction and to support adolescent mental health in an increasingly digital environment.